ECONOMETRIC MODELING: SYNTHESIS OF ICT AND MATHEMATICAL MODELING METHODS - Hlushak, Oksana; Semenyaka, Svetlana (Educological discourse, 2019)
The article presents the theoretical and practical solutions to the problem of the introduction of information and communication technologies in the educational process of teaching economics and mathematical modeling of students of economic and mathematical specialties. It is determined that mathematical modeling with maximum use of its potential enables to identify and solve professional problems of different nature: clearly define the purpose of the research, quickly find possible variants of its achievement, develop appropriate models of economic objects or phenomena and, based on these models, create effective algorithms and programs of optimal ways to solve actual problems. It was established that the electronic study courses of disciplines "Econometrics", "Economic and mathematical modeling" are a complex of educational and methodological materials created for the organization of individual and group training using information and communication technologies, which are aimed at teaching economic and mathematical modeling of students of economic and mathematical specialties. Based on the outlined possibilities of using the e-learning course, as well as its didactic functions, the structure of the electronic training course for the academic disciplines "Econometrics", "Economic-mathematical modeling" on the basis of the Moodle platform was developed and described. The peculiarities of using MS Excel are considered in the example of the task of studying the dependence of the employment rate of the population of Ukraine on the influence of the selected factors. Different stages of construction and research of the econometric model are described: identification of variables, model specification, parametrization and verification on the statistical significance of the obtained results. The prospect of further scientific research is outlined through the effectiveness of the use e-learning courses in order to improve the additional professional competences of future specialists in economic and mathematical specialties.